Intergenerational Mobility, Economic Shocks, and the Role of Human Capital - Patrick Bennett; Jessica Botros (CESifo GmbH, 2024)
How do economic shocks at labor market entry shape patterns of intergenerational mobility? Both family background and negative shocks matter for future labor market success, and these two forces interact with each other. Negative economic shocks disproportionately harm those from disadvantaged backgrounds and, as a result, a one standard deviation increase in unemployment causes an 11–15% decrease in intergenerational mobility. Mobility decreases as higher unemployment widens the pre-existing gap in university education by socioeconomic status, and we show that differences in human capital are a key factor which explain rates of both relative and absolute mobility.
Keywords: 330; Intergenerationenmobilität; Schock; Arbeitslosigkeit; Humankapital; OECD-Staaten